Aspects of the ecology of Bartramia halleriana and Crossocalyx hellerianus in oceanic deciduous woodland in Wales. (1st October 2020) - Callaghan, Des A.; Bevan, Jamie
ABSTRACT: Introduction. This study investigated the ecology of two boreal-montane bryophytes, the saxicolous moss Bartramia halleriana and the epixylic liverwort Crossocalyx hellerianus, at the edge of their ranges, in oceanic deciduous woodland in Wales. Methods. The study site comprises two adjoining woodlands, Allt Penyrhiw-iar (canopy trees ca. 100 yr old) and Allt Rhyd Groes (ca. 200 yr), Carmarthenshire, UK. The distribution and abundance of B. halleriana and C. hellerianus was surveyed, relevés sampled to record habitat and community composition, and sporophyte frequency and stage of development measured. Light climate of B. halleriana was investigated via hemispherical photography, and abundance of large rotten logs used as a measure of habitat quality for C. hellerianus . Results. Four subpopulations of B. halleriana occured, comprising 21 individual-equivalents (occupied 1 m grid cells), all on mildly base-rich mudstone of north-facing rockfaces, with very little direct solar radiation and a diverse assemblage of bryophytes. Sporophytes were scarce. A total of 143 individual-equivalents (occupied logs or trees) of C. hellerianus was recorded, an exceptional population in Wales. Most of the population was within Allt Rhyd Groes, where large rotten logs were much more abundant due to greater woodland age. The liverwort mainly occupied the sides of decorticated rotten logs, amongst a sparse community composed mainly of other small liverworts and Cladonia lichens. Neither sporophytes nor perianths were found on C. hellerianus specimens. Conclusion. Further research could usefully focus on the description and measurement of favourable habitat conditions for each species and associated physiological tolerances to inform conservation decisions for both species.